Half-truth rhetoric and its differences with justification and allusion - Fatemeh Sahraie (مطالعات زبانی و بلاغی)
The present paper aims at familiarizing the readers with the "amphibology" as one of the exquisite figures of speech and describing its difference with justification and allusion. To this purpose, by investigating rhetorical and linguistic books the beauty of this figure of speech and its importance in literary speech were demonstrated and then a brief report of half-truth application in the history of rhetoric, its semantics and types were described. The differences of half-truth with justification and allusion from scholars' viewpoints were addressed and finally the beauty of this figure of speech was demonstrated by providing some examples of literary and historical stories related to amphibology.